First-Time Use of the Seraph® 100 Microbind® Affinity Blood Filter in an Adolescent Patient with Severe COVID-19 Disease: A Case Report - Kyle A. Merrill; Kelli A. Krallman; Daniel Loeb; Stephen W. Standage; Dawn Mattoon; Dandan Shan; Stuart L. Goldstein; Meredith P. Schuh (Case Reports in Nephrology and Dialysis, 2023)
The Seraph® 100 Microbind® Affinity Blood Filter (Seraph® 100) is a hemoperfusion device designed to adsorb bacteria, viruses, and toxins when added to extracorporeal circuits. The FDA granted emergency use authorization in adults, but this device had never been utilized in children. A 17-year-old patient with asthma presented with respiratory distress due to COVID-19. His course was complicated by respiratory failure, rhabdomyolysis, and stage 3 AKI requiring initiation of continuous kidney replacement therapy (CKRT) on ICU day 3. The Seraph® 100 filter was added on ICU day 4. He was treated with 3 filters from ICU day 4 to 8. On ICU day 8, he was extubated and CKRT discontinued. He required no further kidney replacement therapy but did not have laboratory work post-discharge. In conclusion, this adolescent patient with COVID-19 and AKI requiring CKRT tolerated treatment with the Seraph® 100 Microbind® Affinity Blood Filter without significant adverse events.